An autonomic service discovery mechanism to support pervasive devices accessing the semantic grid. (8th April 2009) - Guan, Tao; Zaluska, Ed; Roure, David De
One of the essential challenges of integrating pervasive devices into a grid environment to enhance pervasive device capabilities is that pervasive devices need to locate, find, select and invoke the appropriate grid services in an autonomic and flexible way. However, at this stage, both grid service description and discovery standards are still at an immature stage. This paper presents the research work of building a grid service discovery middleware with semantic web technologies. Semantic web technologies benefit the demand of an efficient discovery of various grid services for pervasive devices by adding machine-processable explicit knowledge into the interaction between pervasive devices and grid services. The middleware has been implemented and interact correctly with other service-oriented pervasive grid middleware, providing an enhanced grid access for pervasive devices.